Clinical Assessment of Early Morning Blood Pressure in Patients with Hypertension - Abdul Awal, Kazi Mohammad; Afrose, Atia; Yesmin, Most Monira; Chowdhuri, Saniut; Alam, Md Shohedul; Ur Rahman, Murshid; Mahmud Manju, Ashek; Rahman, Md Fozlur; Begum, Tania (Medicine Today, 2024)
A significant population experiencing hypertension, blood pressure (BP) demonstrates a significant rise during the awakening hours, it is linked to heightened cardiovascular complications during this time of the day. Many medications used to manage high BP fail to effectively control BP in the early morning, especially when administered once daily in the morning. Key factors to consider when choosing an efficient antihypertensive medication include the agent's pharmacokinetics, formulation, and timing of dosing. Examples of antihypertensive drugs with proven efficacy in regulating early morning BP include medications with extended pharmacologic half-lives, like telmisartan (an angiotensin II receptor blocker), amlodipine (a calcium antagonist), and bisoprolol (a beta-blocker). Administering chronotherapeutic preparations at bedtime has also been shown to be effective in managing early morning BP. There is a correlation between elevated early morning BP and cardiovascular risk, future clinical studies should emphasize evaluating the performance of antihypertensive drugs during this critical period of heightened risk. (Prev Cardiol. 2007;10:210−214) © 2007 Le Jacq. Medicine Today 2023 Vol.36 (1): 55-61